A dendritic hexamer acceptor enables 19.4% efficiency with exceptional stability in organic solar cells - Tao Jia; Tao Lin; Yang Yang; Lunbi Wu; Huimin Cai; Zesheng Zhang; Kangfeng Lin; Yulong Hai; Yongmin Luo; Ruijie Ma; Yao Li; Top Archie Dela Peña; et al. (Nature Communications)
Abstract To achieve the commercialization of organic solar cells (OSCs), it is crucial not only to enhance power conversion efficiency (PCE) but also to improve device stability through rational molecular design. Recently emerging giant molecular acceptor (GMA) materials offer various advantages, such as precise chemical structure, high molecular weight (beneficial to film stability under several external stress), and impressive device efficiency, making them a promising candidate. Here, we report a dendritic hexamer acceptor developed through a branch-connecting strategy, which overcomes the molecular weight bottleneck of GMAs and achieves a high production yield over 58%. The dendritic acceptor Six-IC exhibits modulated crystallinity and miscibility with the donor, thus better morphology performance compared to its monomer, DTC8. Its charge transport ability is further enhanced by additional channels between the armed units. Consequently, the binary OSCs based on D18:Six-IC achieves a cutting-edge efficiency of 19.4% for high-molecular weight acceptor based systems, as well as decent device stability and film ductility. This work reports high-performance OSCs based on dendritic molecule acceptor with a molecular weight exceeding 10000 g/mol and shares the understanding for designing comprehensively high-performing acceptor materials.